A new crystalline daidzein-piperazine salt with enhanced solubility, permeability, and bioavailability - Meng, Jiacheng; Qiu, Chenxu; Lu, Chenyue; He, Xin; Zhao, Xinghua (Frontiers in Pharmacology, 2024)
We respectfully submit our manuscript entitled "A new crystalline Daidzein-piperazine salt with enhanced solubility, permeability and bioavailability" to be considered for publication in Frontiers in Pharmacology. In this study, a novel salt of daidzein (DAI) and piperazine (PIP) was prepared and comprehensively characterized in terms of its structure and physicochemical properties. Additionally, the permeability of DAI-PIP was assessed using the Caco-2 cell model and its pharmacokinetic behavior was explored in beagle dogs. The new salt showed simultaneous enhancement in dissolution, permeability and oral bioavailability of DAI.The animal care and treatment followed the ethics guidelines set by the Animal Welfare Committee of Hebei Agricultural University Ethical Committee. Each author participated sufficiently in the study through conception, design, data analysis and interpretation, drafting and/or editing manuscript.